A structural comparison of supercooled water and intermediate density amorphous ices - Urquidi, J; Benmore, C; Egelstaff, P; Guthrie, M; McLain, SE; Tulk, C; Klug, D; Turner, J (2004)
New data are presented on neutron diffraction in ultrapure bulk supercooled heavy water measured down to 262 K. The data are analysed in terms of the trends observed in the first sharp diffraction peak (FSDP) parameters, the feature which dominates the measured neutron spectra. The neutron FSDP position, height and width are compared to literature data for supercooled water, water under pressure and to the same parameters obtained for recently discovered intermediate density amorphous ices. It is found that the FSDP parameters in supercooled water and the amorphous ices generally exhibit a similar behaviour, suggesting a new structural regime may occur in deeply supercooled water below Q0 ∼ 1.83 Å-1 (T ∼ 251 K) associated with increased intermediate range ordering. It is argued that this structural regime may be linked to a similar trend in the density which appears when the density is plotted as a function of FSDP position. A detailed comparison of the neutron and X-ray structure factors for supercooled water and intermediate density amorphous ices with the same FSDP positions is also made. The diffraction data show that although the overall general structures are qualitatively very similar, the amorphous ice correlations are considerably sharper and extend to much higher radial distances.